Implementation Of Online Mathematics Learning In Vocational Students During Covid-19 - Neng Ariyanti; Anik Yuliani ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
Education is a learning process with the aim of educating to develop self-potential. The Covid-19 pandemic has an impact on the education sector where face-to-face learning becomes online learning. The purpose of this study is to find out the implementation of online math learning in vocational students during the Covid-19 pandemic, in addition to looking at inhibiting factors in the implementation of online learning carried out during the Covid-19 pandemic. The research method used is a qualitative descriptive method. The research was conducted at SMKN 1 Maniis in Purwakarta Regency, the subject of this study was a class XI vocational student with a total of 96 students. The instruments used in the study are non-tests in the form of open questionnaires and interviews. The research procedure is carried out in three stages. (1) the preparatory stage, (2) the implementation stage, (3) the evaluation stage. The results of the study came to several conclusions, that the implementation of online mathematics learning at the time of Covid-19 was carried out in accordance with the curriculum on Covid-19 conditions, and based on the circular of the Minister of Education and Culture number 4 of 2020 on the implementation of education policy. The online math learning process is carried out using interactive applications such as zoom and google meet in addition to also using google classroom and WhatsApp, in the process of implementation teachers provide the next stage of interaction in the form of Q&A and finally the assignment from the teacher. The inhibiting factor in the implementation of online mathematical learning is inadequate internet network that causes the learning process to be hampered which then has an impact on the lack of understanding of the material that has been delivered.